Cassava Skin Usage (Manihot esculenta L.) as Photocatalyst for Degradation of Methylene Blue in the River of Textile Industrial Zone - Kharisma Madda Ellyana; Kharisma Luthfiaratri Rahayu; Ratri Febriastuti; Abdul Haris (Jurnal Kimia Sains dan Aplikasi, 2018)
The progress of the textile industry can increase the amount of dyestuff waste, but often waste disposal is overlooked. The purpose of this research is to provide solution in handling river water pollution by textile industry dye waste. The degradation of textile industry dye waste can be done with TiO2 semiconductors with UV light as a source of irradiation, but only 5% of sunlight can be utilized TiO2 to excite its electrons, so degradation process is not effective. It needs a material that can optimize the activity of TiO2 semiconductor, one of them C-dot coming from cassava skin. The results obtained in this research were TiO2/C-dot composite which could degrade methylene blue where its effectiveness was tested using UV-Vis spectrophotometer instrument. TiO2/C-dot photocatalyst activity test for methylene blue 0.0001 M showed that the concentration of 20% with the amount of degradation up to 96,99%, best type of rays was sunshine with amount of degradation up to 66,25% and longest radiation in sunshine with the amount of degradation was up to 78.77% and UV with the amount of degradation up to 75.99%.